Stress analysis and optimization of quick stop device through finite element analysis using ANSYS - Mohd Zamri, Nur Shahida Azzahra; Amiril, S. A.S. (Penerbit UMP, 2022)
The quick- stop device (QSD) are design for the cutting metal that use in the turning process that produce the chip root formation. This device concentrated on time separation that rapidly stops the cutting when obtain chip root. In the process of cutting chip formation that needed the high impact of force to obtain the high force. The existing QSD designed with large size and weight that to accommodate load more 1000N. The area that high stress maybe can be fatigue when get the force more than the ability of strength of QSD. In this paper an analysis the stress of the critical part of the QSD via explicit dynamic and static structural of QSD with finite element method using ANSYS. In this paper also to study in finding the optimal design using the topology optimization to get the minimize size, design and the weight of the quick-stop device. Then, the values of equivalent stress and total deformation that identify in dynamic and static analysis. From that, it will continue in topology optimization to remove the unnecessary part based on the contour part that the low stress.